2007
DOI: 10.1086/518213
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Planetary Companion around a Nearby Young Star

Abstract: We report evidence for a planetary companion around the nearby young star HD 70573. The star is a G-type dwarf located at a distance of 46 pc. We carried out spectroscopic observations of this star with FEROS at the 2.2 m MPG/ESO telescope at La Silla. Our spectroscopic analysis yields a spectral type of G1-1.5 V and an age of about 100 Myr. Variations in stellar radial velocity (RV) of HD 70573 were monitored from 2003 December until 2007 January. HD 70573 shows an RV variation with a period of ‫)21ע(258‬ day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…FEROS is known to be stable over a fairly long baseline at better than the ∼10 ms −1 level (Setiawan et al 2007) and since we observed each star using the simultaneous ThAr mode we are able to measure accurate radial-velocities that allow us to determine the full kinematic space velocity for each star. In fact we found that the scatter in ThAr lamps themselves did not exceed 300 ms −1 for our entire sampling baseline of three years, highlighting the internal stability of FEROS.…”
Section: Radial-velocitiesmentioning
confidence: 99%
“…FEROS is known to be stable over a fairly long baseline at better than the ∼10 ms −1 level (Setiawan et al 2007) and since we observed each star using the simultaneous ThAr mode we are able to measure accurate radial-velocities that allow us to determine the full kinematic space velocity for each star. In fact we found that the scatter in ThAr lamps themselves did not exceed 300 ms −1 for our entire sampling baseline of three years, highlighting the internal stability of FEROS.…”
Section: Radial-velocitiesmentioning
confidence: 99%
“…Stellar RV variations are produced by different magneticactivity-related phenomena: convection (Saar 2009), starspots , magnetic plage/network (Saar 2003) and flares (Saar 2009;Reiners 2009). Although bisector analysis may sometimes lead to the confirmation of a planet orbiting a star even when RV jitter is present (Sozzetti et al 2006;Setiawan et al 2007Setiawan et al , 2008, the latter technique is not always successful (Huélamo et al 2008;Figueira et al 2010). Several authors have studied the impact of activity on RV jitter using R HK as a proxy (Saar et al 1998;Santos et al 2000;Paulson et al 2002;Saar et al 2003;Wright 2005;Paulson & Yelda 2006;Santos et al 2010).…”
Section: Predicted Radial Velocity Jittermentioning
confidence: 99%
“…In the last few years, several young planet detection surveys have been conducted in PMS stars using different techniques, such as direct imaging (e.g., Lafrenière et al 2010;Kraus & Ireland 2012) or radial velocity (RV) monitoring (e.g., Martín et al 2006;Setiawan et al 2007;Crockett et al 2012). To deploy RV surveys on young low-mass stars (which are considerably faint, distant and affected by extinction) is, in most of cases, an arduous task.…”
Section: Introductionmentioning
confidence: 99%